2023
DOI: 10.3390/su15097484
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Changes and Microbiome Associations during Vermicomposting of Winery Waste

Abstract: Annually, the wine industry produces high amounts of waste that can be toxic if disposed of without pretreatment. Vermicomposting is an efficient and low-cost method of decomposing organic matter using earthworms under controlled conditions. The organic substrate used in the vermicomposting process affects microbial populations and reflects the dynamics of enzymatic activity, decomposition of organic matter, and nitrogen transformations. However, the microbiome associations during the whole process are still u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 80 publications
0
5
1
Order By: Relevance
“…The content of Ca varied in the range from 3.89% ± 0.02 (E4) to 5.38% ± 0.03 (E1). The obtained Ca values in this study were higher than those reported by [66] (less than 2.5%) or Karapantzou et al [67] (less than 1.86%), possibly as a result of the Ca levels in the initial substrates or the duration of the composting process. The content of K increased during vermicomposting, reaching values at the end of the process of 0.69% ± 0.47−0.97%± 0.02.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…The content of Ca varied in the range from 3.89% ± 0.02 (E4) to 5.38% ± 0.03 (E1). The obtained Ca values in this study were higher than those reported by [66] (less than 2.5%) or Karapantzou et al [67] (less than 1.86%), possibly as a result of the Ca levels in the initial substrates or the duration of the composting process. The content of K increased during vermicomposting, reaching values at the end of the process of 0.69% ± 0.47−0.97%± 0.02.…”
Section: Discussioncontrasting
confidence: 85%
“…The number of sulfate-reducing clostridia (except in treatments E1 and E2 at the beginning of the experiment) was below 10 2 CFU/g in all the treatments (Table 4). The reduction and elimination of these bacteria, as described by other researchers [67], are partly the result of the indirect activities of the earthworms. In other words, changes in the physical conditions of the substrate during the vermicomposting process, through the continuous aeration facilitated by earthworms, directly impact these anaerobic bacteria [28].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Vermicomposting (organic matter transformation by earthworms) is another viable biotechnology for the treatment of wine organic wastes, as demonstrated by several studies (Gómez-Brandón et al, 2021Karapantzou et al, 2023;Paradelo et al, 2011). Thus, the potential valorisation of by-products generated during wine production enables the recycling of organic matter and nutrients, fostering sustainable viticulture within a circular economy framework.…”
Section: Anaerobic Digestion Technology Represents Another Opportunitymentioning
confidence: 99%